Are housing and neighbourhood empowerment beneficial for mental health and wellbeing? Evidence from disadvantaged communities experiencing regeneration. (December 2020) - Kearns, Ade; Whitley, Elise
Abstract: Community engagement and empowerment are central to delivery and outcomes from regeneration programmes, yet evidence for health gains in such contexts is sparse and mixed. This study addresses this issue in respect of mental health and wellbeing in disadvantaged communities in the UK, using a sample of 2862 householders living through housing improvements and regeneration in Glasgow. Feelings of empowerment were more strongly associated with mental wellbeing (WEMWBS) than mental health (SF-12 MCS). Neighbourhood empowerment was more strongly associated with mental wellbeing and mental health than housing empowerment, although its association with mental health disappeared in the period of welfare reform and austerity. Proactive forms of empowerment, such as influencing decisions affecting an area or taking action oneself to improve things, were more strongly associated with mental wellbeing than reactive or passive forms of empowerment. There is much scope to improve feelings of empowerment in disadvantaged communities and to contribute to national objectives to enhance mental wellbeing.